Music tempo's effect on exercise performance: comment on dyer and mckune - Nakamura, Priscila Missaki [UNESP] (Ammons Scientific, Ltd, 2015)
Dyer and McKune (2013) stated that music tempo has no influence on performance, physiological, and psychophysical variables in well-trained cyclists during high intensity endurance tasks. However, there are important limitations in the methodology of the study. The participants'music preferences and tempo change were not well measured. It is not possible to affirm that music tempo does not influence athletes'performance. Potential areas of future research include: (a) use of instruments to assess the qualities of music; (b) standardizing music of tempo according to exercise type (e.g., running, cycling, etc.); (c) considering training level of the participants (i.e., athletes and non-athletes); and (d) use of instruments to assess concentration during exercise.